Mengenal Self-Confession dalam Pribadi Berkarakter - Nasution, Atikah Rahmah; Mapilindo, Mapilindo (Universitas Batanghari Jambi, 2024)
This research uses a qualitative descriptive method with a literature review or literature study type of research. The aim of this research is to collect information or scientific papers by describing existing phenomena related to self-confession and personal character. The results of this research show that self-confession can influence a person's personal character, where self-confession has a negative side that will arise from a student's behavior.